PENGGUNAAN MODEL PEMBELAJARAN GUIDED NOTE TAKING UNTUK MENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR IPA SISWA KELAS VII B SMP NEGERI 11 YOGYAKARTA - Nofi Elistina (N A T U R A L: Jurnal Ilmiah Pendidikan IPA, 2016)
The objective of this study is to improve students’ activity and science learning outcome at VII B grade students through a learning model Guided Note Taking in SMP N 11 Yogyakarta in academic year 2013/2014. This study belongs to Classroom Action Research (CAR). Observation, test, interview, and documentation are used to gather the data in this study. The results of the study show that after implementing the Guided Note Taking model at VII B class in SMP N 11 Yogyakarta, students’ activity and learning outcome increase. It is shown by the increase of students’ percentage in observation sheets in each cycle. In the first cycle, the average of the activity indicator increased 13% from 73% to 86% in the second cycle. The science-learning outcome increased from 54,38 before the treatment, 66,86 in the first cycle, and became 80,78 in the second cycle. The number of students who passed the passing grade before the treatment was only 1 student or 2,94%. In cycle I, there was 19 students or 55,88% who passed the KKM, and there were 27 students or 79,41% in the cycle II.